Phenotypes and genetic etiology of spontaneous polycystic kidney and liver disease in cynomolgus monkey - Wu, Ruo; Bai, Bing; Li, Feng; Bai, Raoxian; Zhuo, Yan; Zhu, Zhengna; Jia, Rongfang; Li, Shangang; Chen, Yongchang; Lan, Xiaoping (Frontiers in Veterinary Science, 2023)
Introduction Polycystic kidney disease (PKD) is a common autosomal dominant or recessive genetic disease, often accompanied by polycystic liver disease (PLD). Many cases of PKD in animals have been reported. However, little is known about the genes that cause PKD in animals. Methods In this study, we evaluated the clinical phenotypes of PKD in two spontaneously aged cynomolgus monkeys and explored the genetic etiology using whole-genome sequencing (WGS). Ultrasonic and histological consequences were further investigated in PKD- and PLD-affected monkeys. Results The results indicated that the kidneys of the two monkeys had varying degrees of cystic changes, and the renal cortex was thinned and accompanied by fluid accumulation. As for hepatopathy, inflammatory cell infiltration, cystic effusion, steatosis of hepatocytes, and pseudo-lobular were found. Based on WGS results, the variants of PKD1:(XM_015442355: c.1144G>C p. E382Q) and GANAB: (NM_001285075.1: c.2708T>C/p. V903A) are predicted to be likely pathogenic heterozygous mutations in PKD- and PLD-affected monkeys. Discussion Our study suggests that the cynomolgus monkey PKD and PLD phenotypes are very similar to those in humans, and are probably caused by pathogenic genes homologous to humans. The results indicate that cynomolgus monkeys can be used as the most appropriate animal model for human PKD pathogenesis research and therapeutic drug screening.